Tunable Emission in Heteroepitaxial Ln‐SURMOFs. (10th July 2019) - Chen, Dong‐Hui; Haldar, Ritesh; Neumeier, Beatrice Lilli; Fu, Zhi‐Hua; Feldmann, Claus; Wöll, Christof; Redel, Engelbert
Abstract: By using a layer‐by‐layer (LbL) approach, lanthanide‐based, monolithic metal–organic framework (MOF) thin films are fabricated for optical applications. In particular, the LbL approach allows manufacturing of heteroepitaxial Tb(III)‐Eu(III)(BTC) coatings with precise thickness control. Adjusting the Tb(III)‐to‐Eu(III) ratio allows tuning of the emission color. The hetero‐multilayer architecture makes it possible to suppress the direct Tb(III)‐to‐Eu(III) energy transfer, an unwanted phenomenon present in the corresponding mixed‐metal bulk MOF structures. The resulting Ln‐MOF thin films, or Ln‐surface‐anchored MOFs (SURMOFs), are characterized by X‐ray diffraction, infra‐red reflection absorption spectroscopy, UV–vis, and photoluminescence measurements. The results demonstrate that the heteroepitaxial SURMOF architectures carry huge potential for fabricating optical coatings for a wide range of applications. Abstract : The first lanthanide‐based, oriented and crystalline surface‐anchored metal–organic frameworks (MOFs) are fabricated via a layer‐by‐layer approach. Adjusting the ratio of the heteroepitaxial bilayer Tb(III)‐Eu(III)(BTC) can tune the emission color. The hetero‐multilayer architecture reduces the Tb(III)‐to‐Eu(III) energy transfer and results in an optimized fabrication of Ln‐MOF thin films with straightforward modulation of the emission color.